1971
DOI: 10.1002/cpt1971121105
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of lidocaine in man

Abstract: Plasma levels of lidocaine were measured in 5 normal male volunteers following both intravenous and oral administration of the drug. Each subject received a constant-rate intravenous infusion lasting for 60 minutes and an exponential intravenous infusion which allowed administration of the drug at an ever-decreasing rate having a half-life of 50 minutes.In each case the total dose of lidocaine was 250 mg. The subjects also received a 250 mg. and a 500 mg. oral dose administered in tablet form. The plasma level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
2
1

Year Published

1976
1976
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(68 citation statements)
references
References 7 publications
2
63
2
1
Order By: Relevance
“…To ensure that the lignocaine dose we used was effective in controlling pain and had minimal risk for adverse event, we decided to use 3 mL of 1% lignocaine for in our study. Furthermore, Lim et al (14) has shown that this dose of lignocaine was effective for pain control both immediately and throughout a 2-hour infusion period, attributable to the duration of action of lignocaine [t 1/2 , 80-108 minutes (20,21)]. With the increased in sample size, our study had shown that lignocaine was able to reduce to pain associated with potassium chloride infusion.…”
Section: Resultssupporting
confidence: 49%
“…To ensure that the lignocaine dose we used was effective in controlling pain and had minimal risk for adverse event, we decided to use 3 mL of 1% lignocaine for in our study. Furthermore, Lim et al (14) has shown that this dose of lignocaine was effective for pain control both immediately and throughout a 2-hour infusion period, attributable to the duration of action of lignocaine [t 1/2 , 80-108 minutes (20,21)]. With the increased in sample size, our study had shown that lignocaine was able to reduce to pain associated with potassium chloride infusion.…”
Section: Resultssupporting
confidence: 49%
“…Although this assumption is substantiated by carefully conducted stuLdies both in animals (Keenaghan & Boyes, 1972;Boyes eIla., 1970) and in man (Boyes et al, 1971;Huet ct al., 1979), it may not necessarily hold true for all experimental conditions in which the test could possibly be used.…”
Section: Methodsmentioning
confidence: 99%
“…Under these conditions, and provided absorption is complete and metabolism is first-order, any change in hepatic drug metabolizing capacity will result in proportional but opposite changes in the oral bioavailability of the drug (Wilkinson & Shand, 1975;Alvan, Piafsky, Lind & von Bahr, 1979;Sotaniemi et al, 1978;Perucca & Richens, 1979a,b;Pantuck, Hsiao, Conney, Garland, Kappas, Anderson & Alvares, 1976) which, in turn, can be used as an indirect index of enzyme-induction or inhibition. Although the theoretical aspects of these principles have been considered in detail (Wilkinson & Shand, 1975;Perrier & Gibaldi, 1974;Rowland, 1972) (Stenson, Constantino & Harrison, 1971), primarily due to metabolic biotransformation by an enzymatic system which involves the mixed function oxidase (Strong, Parker & Atkinson, 1973;Hollunger, 1960;Keenaghan & Boyes, 1972) and has been shown to be inducible in animals (Di Fazio & Brown, 1972) and in man (Perucca & Richens, 1979b;Heinonen, Takki & Jahro, 1979); ii) virtually complete absorption from the gastrointestinal tract (Keenaghan & Boyes, (Bending, Bennett, Rowland & Steiner, 1976;Perucca, 1979;Boyes et al, 1971); iv) its previous use as a model drug in experiments designed to evaluate the perfusion-limited pharmacokinetic model in animals (Rane, Wilkinson & Shand, 1977;Branch, Shand, Wilkinson & Nies, 1973;Benowitz, Forsyth, Melmon & Rowland, 1974) and in man (Perucca & Richens, 1979b). This study provides further evidence in support of the hypothesis that the reduction of the oral bioavailability of lignocaine in epileptic patients is due to induction of the first-pass metabolism of the latter drug (Perucca & Richens, 1979b).…”
Section: Introductionmentioning
confidence: 99%
“…Lignocaine is almost ideal as a model drug because (i) it is subject to high hepatic clearance in man, as indicated by a high liver extraction ratio (Stenson, Constantino & Harrison, 1971) and evidence of extensive first-pass metabolism on oral administration (Boyes, Scott, Jebson, Godman & Julian, 1971;Bending, Bennett, Rowland & Steiner, 1976); (ii) it is metabolized by an enzymatic system in the liver which involves the mixed function oxidase (Hollunger, 1960; K^enaghan & Boyes, 1972; Bahr, Fellenius 8' Ft .d, 1972;Strong, Parker & Atkinson, 1973) and which is induced by phenobarbitone treatment the dog (Di Fazio & Brown, 1972); (iii) it has been previously selected to test the perfusion limited model in animal studies (Branch, Shand, Wilkinson & Nies, 1973;Benowitz, Forsyth, Melmon & Rowland, 1974a;Benowitz, Forsyth, Melmon & Rowland, 1974b;Rane, Wilkinson & Shand, 1977) and (iv) it is relatively safe at the plasma concentrations achieved in our subjects. This study adds further information to the question of lignocaine bioavailability on oral administration.…”
Section: Introductionmentioning
confidence: 99%